Innovative Thermal Insulation Products for a Circular Economy. (June 2019) - Vasile, V; Petcu, C; Meiţă, V; Zaharia, M C
Abstract: The depletion of non-renewable resources is followed by severe ecological and social impacts, and the heavily usage of raw, virgin resources leaves significant, long lasting footprints. In order to move into a more sustainable economic system, a recently more frequently discussed approach for overcoming the current linearity of product lifecycles is the concept of circular economy (CE). The transition to a more circular economy, where the value of products, materials and resources is maintained and circulated (by recycling activities) in the economy for as long as possible, is an essential contribution to the EU's efforts to develop a sustainable, low carbon, resource efficient and competitive economy. In this context, ecological solutions consisting of materials which helps carbon sequestration and necessitates small amounts of energy for production are becoming increasingly popular from buildings construction point of view, namely: the raw material is cheap and in large quantities; have low thermal conductivity; are from a renewable source. The paper presents an analysis of some innovative thermal insulating products made from renewable or recycled resources (recycled plastics, low quality wool, straw, cellulose), their thermal conductivities over a temperature interval and acoustics coefficients (αs, αw ), the purpose being to inform the market in order to increase the present level of technical knowledge and to facilitate the implementation of high energy efficiency buildings with products from recycled materials or using industrial by-products.